2018
DOI: 10.1007/978-3-319-92108-2_20
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Applicability of Elaborateness and Indirectness in Dialogue Management

Abstract: In this paper, we investigate the applicability of soft changes to the system behaviour, namely changing the amount of elaborateness and indirectness displayed. To this end, we examine the impact of elaborateness and indirectness on the perception of human-computer communication in a user study. Here, we show that elaborateness and indirectness influence the user's impression of a dialogue and discuss the implications of our results for adaptive dialogue management. We conclude that elaborateness and indirectn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Meanwhile, different descriptions of the same data may lead to different outcomes. For example, Pragst et al [13] demonstrated that different levels of elaborateness and indirectness can influence users' perceptions of the information provided.…”
Section: A Technology-based Behavior Change Promotionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, different descriptions of the same data may lead to different outcomes. For example, Pragst et al [13] demonstrated that different levels of elaborateness and indirectness can influence users' perceptions of the information provided.…”
Section: A Technology-based Behavior Change Promotionmentioning
confidence: 99%
“…One adaption approach is keeping the propositional content of a system action the same and changing only the way it is presented, i.e., the communication style. Pragst et al [13] investigated the applicability of elaborateness and indirectness as possibilities for adaptation in human-computer interaction. They found that these dimensions influence the user's perception of dialogue and are therefore valuable candidates for adaptive dialogue management.…”
Section: B Adaptive Communication Stylesmentioning
confidence: 99%
See 1 more Smart Citation
“…These works compared lab experiments with crowdsourced ones -in the scenario of spoken dialogue systems -showing that the results in the former (direct interaction with the system) are comparable with the results in the latter (third party users reading transcriptions). Similarly, in (Pragst et al, 2017), the authors focus on a WoZ evaluation of the interaction strategies of an embodied conversational agents. Users were presented with the video of an embodied conversational agent interacting with a human user (the agent was guided by a Wizard and the user was an instructed actor).…”
Section: Related Workmentioning
confidence: 99%
“…Studies could show that under specific circumstances indirectness is preferred not only from human conversation partners, but also in human-computer interaction (e.g. (Miehle et al, 2016;Pragst et al, 2017)). Therefore, dialogue systems that can adjust the level of directness in their output to the user and their circumstances should be able to provide an improved user experience.…”
Section: Introductionmentioning
confidence: 99%